A Quality by Design Framework for Capsule-Based Dry Powder Inhalers - Li Ding; Ashlee D. Brunaugh; Sven Stegemann; Scott V. Jermain; Matthew J. Herpin; Justin Kalafat; Hugh D. C. Smyth (MDPI AG, 2021)
Capsule-based dry powder inhalers (cDPIs) are widely utilized in the delivery of pharmaceutical powders to the lungs. In these systems, the fundamental nature of the interactions between the drug/formulation powder, the capsules, the inhaler device, and the patient must be fully elucidated in order to develop robust manufacturing procedures and provide reproducible lung deposition of the drug payload. Though many commercially available DPIs utilize a capsule-based dose metering system, an in-depth analysis of the critical factors associated with the use of the capsule component has not yet been performed. This review is intended to provide information on critical factors to be considered for the application of a quality by design (QbD) approach for cDPI development. The quality target product profile (QTPP) defines the critical quality attributes (CQAs) which need to be understood to define the critical material attributes (CMA) and critical process parameters (CPP) for cDPI development as well as manufacturing and control.